The effect of first step etching times on diamond coating of tungsten carbide [electronic resource] - 412652 Zahrul Adnan Mat Taib (2009)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal-Pembuatan)) - Universiti Teknologi Malaysia, 2009